Employment in public sector: Empirical evidence from Georgia - Egnate Shamugia (CES Working Papers, 2023)
This paper aims to assess employment in Georgia's public sector and study job creation factors. During the last decade, employment in the public sector has increased, and its share in total employment is, on average, 22.5%. This figure is high considering the real expenditures of the government, and the amount of delivered goods and services since some countries like Georgia ensure the provision of public services with relatively fewer human resources. On the other hand, the paper demonstrates job creation factors in the sector through regression analysis. Such a factor is politicians' rent-seeking - creating jobs for influential groups and ensuring political stability. This is more characteristic of those countries that lack democracy and the rule of law.
Keywords: 330; employment; public sector; rent seeking; public finance